Open Innovations - Situation, Conditions, and Activity of Enterprises - de Pourbaix , Paweł; Warzybok , Agnieszka (Studia Oeconomica Posnaniensia, 2018)
The topic of the paper is related to the innovative issues in innovation literature, i.e. open innovation. It should be noted that the ability to absorb knowledge and ideas from external sources and create new products and services based on market needs is becoming one of the key factors determining the development potential of companies and the application of marketing tools. Approaches to open innovation with external stakeholders can take on a variety of forms and, above all, vary from inspiration from the customer and the pursuit of further stages in the process of internal forces, to the organization of an enterprise in the form of an open venture. The authors' task is to identify ways of creating innovations based on the company's dialogue with external stakeholders. Initial reflections are devoted to the theoretical aspects of conceptualization of the term "innovation", "open innovation", and the factors that influence their development. The paper presents the results which are aimed at presenting the specifics, determinants and activity of enterprises which use open innovation with the participation of external entities. The importance of open innovations for shaping selected marketing activities of the surveyed enterprises was also emphasized.